2014
DOI: 10.5547/01956574.35.si1.4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects of Market-Based and Command-and-Control Policies

Abstract: Scientific evidence indicates that greenhouse gases emissions related to human activity are a significant contributor to global climate change. This paper investigates the impact of policy prescriptions and technologies for reducing U.S. greenhouse gas emissions. The analysis uses NERA's N ew ERA integrated model, which combines a top-down general equilibrium macro model of the U.S. economy with a detailed bottom-up model of the North American electricity sector. It examines the cost of cutting emissions by 0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Rather, as widely recognized in economics literature, "internalizing externalities" is most efficiently achieved by directly pricing those externalities rather than through technology-or sector-specific policies. This is in part due to possible economy-wide rebound, spillover, or leakage effects and also because such policies more directly target the achievement of public benefits (Borenstein 2012;IPCC 2011;IPCC 2014a;Kalkuhl et al 2013;McKibbin et al 2014;Tuladhar et al 2014).…”
Section: • Considering Costs In the Equationmentioning
confidence: 99%
“…Rather, as widely recognized in economics literature, "internalizing externalities" is most efficiently achieved by directly pricing those externalities rather than through technology-or sector-specific policies. This is in part due to possible economy-wide rebound, spillover, or leakage effects and also because such policies more directly target the achievement of public benefits (Borenstein 2012;IPCC 2011;IPCC 2014a;Kalkuhl et al 2013;McKibbin et al 2014;Tuladhar et al 2014).…”
Section: • Considering Costs In the Equationmentioning
confidence: 99%
“…The specific costs and benefits of increased wind development will be impacted by the nature of the policy and market levers used to encourage that development; as such, the present work suggests the general magnitude of these impacts only. Related research has found that policies specifically designed to internalize external costs and correct for market failures are likely to be more cost effective than technology-or sector-specific policy incentives, in part due to possible economy-wide rebound and spillover effects and also because such policies more-directly target the achievement of public benefits (Borenstein 2012;Edenhofer et al 2013;Fischer and Newell 2008;Fell and Linn 2013;IPCC 2011;IPCC 2014b;Kalkuhl et al2013;McKibbin et al 2014;Novan 2014;Rausch and Karplus 2014;Tuladhar et al 2014). Therefore, while the present analysis may suggest a significantly positive role for wind energy, achieving those benefits to the maximum and most cost-effective degree is likely to require a policy framework that moves away from direct support of wind to one that more effectively and more broadly addresses key market failures and unpriced externalities.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, as widely recognized in the economics literature, "internalizing externalities" is generally most cost-effectively achieved by directly pricing those externalities rather than through technology-or sector-specific policies. This is partly due to possible economy-wide rebound, spillover, or leakage effects, and also because such policies more directly target the achievement of public benefits (Borenstein 2012;Edenhofer et al 2013;IPCC 2011;IPCC 2014;Kalkuhl et al 2013;McKibbin et al 2014;Tuladhar et al 2014). Research focused on RPS policies has highlighted these possible effects, finding that the desired benefits of RPS programs may not be fully achieved or achieved as cost effectively as might be desired (Bushnell et al 2007;Carley 2011;Fischer and Newell 2008;Fell and Linn 2013;Rausch and Karplus 2014), though other research suggests that the pitfalls of such "second-best" policies may be modest (Kalkuhl et al 2012).…”
Section: General Limitationsmentioning
confidence: 99%